High Levels of Systemic Inflammatory Markers Associated with Metastasis Incidence in Osteosarcoma - Wiratnaya, I. Gede Eka; Ismail, Mohamad Dimas; Raditya, Risang Haryo; Prasetya, I. Putu Dema (Revista Brasileira de Ortopedia, 2025)
The present study explores the association between these inflammatory markers and metastasis in osteosarcoma patients.We conducted a retrospective analysis of osteosarcoma patients at our center between January 2022 and August 2024. We collected the clinical and laboratory data of the patients, including white blood cell differential count, C-reactive protein (CRP) levels, erythrocyte sedimentation rate (ESR), neutrophil-to-lymphocyte ratio (NLR), alkaline phosphatase (ALP) and lactate dehydrogenase (LDH) levels. Statistical correlation between these markers and metastasis was assessed using the Pearson's Chi-squared test, the Fisher's exact test, and logistic regression.A total of 40 osteosarcoma patients were included. Elevated levels of neutrophil count (p = 0.024; odds ratio [OR] = 12.667; 95%CI = 1.402–114.419), CRP (p < 0.001; OR = 17.000; 95%CI = 3.464–83.436), ESR (p = 0.009; OR = 19.000; 95%CI = 2.119–170.383), NLR (p = 0.006; OR = 7.429; 95%CI = 1.778–31.040), and LDH (p = 0.009; OR = 9.333; 95%CI = 2.180–39.962) were significantly associated with the presence of metastasis.The neutrophil count, ESR, NLR, and the levels of CRP and LDH are significantly associated with metastasis in osteosarcoma, and they may serve as valuable prognostic markers. Future research should focus on elucidating the mechanisms underlying this relationship and exploring therapeutic interventions targeting inflammation to mitigate metastasis.
Keywords: blood sedimentation; bone neoplasms; C-reactive protein; L-lactate dehydrogenase; osteosarcoma